Potret Kehidupan Masyarakat Transmigran Bali di Desa Sumber Makmur Kecamatan Satui Kabupaten Tanah Bumbu - Amitasari, Noor; Prawitasari, Melisa; Akmal, Helmi (Lambung Mangkurat University, 2021)
The background of this research describes the process of arrival of Balinese transmigrants in Sumber Makmur Village, Satui District, Tanah Bumbu Regency along with their social and religious life. The research was made with the aim of knowing how the life of the Balinese transmigrant community in Sumber Makmur Village. The method used in this research is the historical method, namely heuristics, criticism, interpretation, and historiography. Primary sources are obtained directly from sources about the object under study. Data collection techniques through observation, interviews, and documentation. Secondary sources are obtained from literature studies, in the form of useful notes with the object of research. The results of field research, it shows that since the Balinese came to Sumber Makmur Village in 1983, the development of Balinese society at that time was still in the construction stage starting from establishing settlements, to buildings of worship (temples). In 2000, the buildings owned by residents were better. Their life is relatively harmonious, although there are slight adjustments because it is not completely the same as on the island of Bali which is thick with Hindu culture. However, this did not change their previous culture and beliefs. The results of this study indicate that the life of the Balinese transmigrants in Sumber Makmur Village is running well and there is no conflict, so that their lives as migrants remain harmonious.